Implementing Various Interaction Patterns in Teaching English Skills - Vinde Rambe, Sokhira Linda (ELITE JOURNAL, 2023)
ABSTRACT This study talked about interaction patterns in EFL teaching and learning context which aims to explore types of interaction patterns implemented by the teachers in teaching English skills. The problem in this study was formulated into “what types of interaction patterns do the teachers use in teaching English skills? The research in this study was in a form of qualitative descriptive research. This study conducted research toward three qualified English teachers at Language Development Center of IAIN Padangsidimpuan together with the students who study English with them. The instruments used were observation and interview. This study found that there were some interaction patterns applied by the teachers in teaching English skills. In teaching speaking and reading, the teachers often use full class interaction, group work, and pair work. In teaching writing, group work, individual work, and full class interaction are often used. Finally, in teaching listening, pairs and individual work are frequently applied. From these interaction patterns, there are two patterns dominantly used by the teachers i.e. group work and full class interaction. Keywords: interaction. patterns